Lasiocepsin, a novel cyclic antimicrobial peptide from the venom of eusocial bee Lasioglossum laticeps (Hymenoptera: Halictidae) - Monincová, Lenka; Slaninová, Jiřina; Fučík, Vladimír; Hovorka, Oldřich; Voburka, Zdeněk; Bednárová, Lucie; Maloň, Petr; Štokrová, Jitka; Čeřovský, Václav (Amino acids, 2012)
In the venom of eusocial bee Lasioglossum laticeps, we identified a novel unique antimicrobial peptide named lasiocepsin consisting of 27 amino acid residues and two disulfide bridges. After identifying its primary structure, we synthesized lasiocepsin by solid-phase peptide synthesis using two different approaches for oxidative folding. The oxidative folding of fully deprotected linear peptide resulted in a mixture of three products differing in the pattern of disulfide bridges. Regioselective disulfide bond formation significantly improved the yield of desired product. The synthetic lasiocepsin possessed antimicrobial activity against both Gram-positive and -negative bacteria, antifungal activity against Candida albicans, and no hemolytic activity against human erythrocytes. We synthesized two lasiocepsin analogs cyclized through one native disulfide bridge in different positions and having the remaining two cysteines substituted by alanines. The analog cyclized through a Cys8-Cys25 disulfide bridge showed reduced antimicrobial activity compared to the native peptide while the second one (Cys17-Cys27) was almost inactive. Linear lasiocepsin having all four cysteine residues substituted by alanines or alkylated was also inactive. That was in contrast to the linear lasiocepsin with all four cysteine residues non-paired, which exhibited remarkable antimicrobial activity. The shortening of lasiocepsin by several amino acid residues either from the N- or C-terminal resulted in significant loss of antimicrobial activity. Study of Bacillus subtilis cells treated by lasiocepsin using transmission electron microscopy showed leakage of bacterial content mainly from the holes localized at the ends of the bacterial cells.
Keywords: Microbial Sensitivity Tests; Humans; Protein Structure, Secondary; antifungální látky; Erythrocytes; Hemolysis; Molecular Sequence Data; Sequence Analysis, Protein; molekulární sekvence - údaje; Bee Venoms; mikrobiální testy citlivosti; lidé; antibakteriální látky; zvířata; sekundární struktura proteinů; Cystine; včely; sekvenční analýza proteinů; cyklické peptidy; Amino Acid Sequence; cystin; Anti-Bacterial Agents; Peptides, Cyclic; Antifungal Agents; Bees; erytrocyty; Gram-Negative Bacteria; grampozitivní bakterie; Candida albicans; Animals; Gram-Positive Bacteria; hemolýza; gramnegativní bakterie; včelí jedy; sekvence aminokyselin